The Mechanical Alloying Behavior of Fe2O3 into NiO in the High-Energy Ball-Milling Process - Y. Z. Zhu; Y. Liu; H. Huang; Y. Y. Guo; S. Y. Yin; F. W. Hu (Advances in Materials Science and Engineering)
The NiO and Fe2O3 powders were mixed by the high-energy ball-milling, followed by a sintering of the mixture at 1340°C for 0.5 h. XRD, SEM, DSC, and size measurements were preformed to study the microstructure evolution in the high-energy ball-milled mixture and the sintered ones, as well. It showed that the high-energy ball-milling processes resulted in a severe lattice distortion in the powder of Fe2O3, but only a slight lattice distortion in NiO. Meanwhile, a solid solution of iron atoms into the NiO lattice was also detected in the milling process. It was also found that the solubility of the iron atoms into the NiO lattice delayed the synthesizing reaction in the following sintering process.